Dinamika Inflasi Di Indonesia Terhadap Daya Beli Masyarakat Pada Tinjauan Ekonomi Makro - Anas Wahid Maulana; Isnan Sayid Maulana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Analysis of the influence of inflation dynamics in Indonesia on people's purchasing power is an important focus in macroeconomic studies. This research aims to explore the impact of inflation on people's purchasing power in the Indonesian macroeconomic context. The research method used is qualitative, involving observation and interviews by researchers. The research stages are data reduction to shorten, focus and reduce less important things and process the data in such a way that the final conclusion is implemented. From the results of observations and interviews, it can be concluded that the macroeconomic review of inflation in Indonesia illustrates the complex relationship between this phenomenon and people's purchasing power. High inflation can put significant pressure on consumers' ability to purchase goods and services, while moderate inflation with the right policies can provide opportunities for balanced economic growth.